What’s in a Moment: What Can Be Learned About Pair Bonding From Studying Moment-To-Moment Behavioral Synchrony Between Partners? - Prior, Nora H. (Frontiers in Psychology, 2020)
Our understanding of the behavioral and physiological mechanisms of monogamy largely comes from studies of behavioral interactions unique to pair-bonded individuals. By focusing on these highly marked behaviors, a remarkable conservation in the mechanisms underlying pair bonding has been revealed; however, we continue to know very little about the range of behavioral and neurobiological mechanisms that could explain the great diversity of pair-bonding phenotypes that exists both within and across species. In order to capture the dynamic nature of bonds over time and across contexts, we need specific, operationally defined behavioral variables relevant across such a diversity of scenarios. Additionally, we need to be able to situate these behavioral variables within broader frameworks that allow us to interpret and compare patterns seen across species. Here I review what is known about behavioral synchrony with respect to pair bonding and discuss using synchrony as such a variable as well as a framework to expand on our understanding of pair bonding across timescales, contexts and species. First, I discuss the importance of behavioral synchrony and parental coordination for reproductive success in monogamous biparental bird species. Second, I highlight research documenting the critical importance of interpersonal coordination for human social relationships. Finally, I present recent work that experimentally bridges these lines of research by quantifying moment-to-moment behavioral synchrony during brief social interactions in zebra finch dyads. All together, these distinct perspectives support the notion that synchrony (1) is a shared premise for sociality across species, (2) is deeply shaped by social experiences, and (3) exists across timescales, behaviors, and levels of physiology. Conceptualizing pair bonding through the framework of behavioral synchrony is likely to facilitate a deeper understanding of the nuances of how social experiences and interactions impact the brain and behavior.